2004
DOI: 10.1603/0022-2585-41.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the VecTest Malaria Antigen Panel Assay for the Detection ofPlasmodium falciparumandP. vivaxCircumsporozoite Protein in Anopheline Mosquitoes in Thailand

Abstract: We evaluated the performance of the VecTest Malaria Antigen Panel (V-MAP) assay for the detection of Plasmodium falciparum and P. vivax (variants 210 and 247) circumsporozoite protein in anopheline mosquitoes in Thailand. The V-MAP assay is a rapid, one-step procedure using a 'dipstick' wicking test strip. The circumsporozoite (CS) ELISA was used as the reference standard. Mosquitoes evaluated in the study included field-collected specimens (n = 930) and laboratory-reared specimens that had been fed on blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…annularis were fed on human blood, while 2.6% were found positive for Plasmodium falciparum malaria parasite [ 6 ]. VectorTest ™ antigen panel assay has been found effective in monitoring the disease spread by detecting malaria parasite in the wild collected mosquitoes [ 24 , 25 ]. The used assay is rapid, one step procedure and qualitatively identifies specific peptide epitopes of circumsporozoites of the types of Plasmodium sporozoites.…”
Section: Discussionmentioning
confidence: 99%
“…annularis were fed on human blood, while 2.6% were found positive for Plasmodium falciparum malaria parasite [ 6 ]. VectorTest ™ antigen panel assay has been found effective in monitoring the disease spread by detecting malaria parasite in the wild collected mosquitoes [ 24 , 25 ]. The used assay is rapid, one step procedure and qualitatively identifies specific peptide epitopes of circumsporozoites of the types of Plasmodium sporozoites.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the included studies was assessed using the STROBE checklist (Additional file 3 : Table S3). For the included studies identified from the three databases, most of the studies (14/19, 73.7%) [ 20 , 23 , 37 – 42 , 44 – 48 , 51 ] were of moderate quality, whereas four (21.1%) were of high quality [ 15 , 16 , 36 , 43 ] and one study (5.26%) [ 19 ] was of low quality. For the included studies identified from the reference lists and Google Scholar, most of the studies (9/12, 75%) [ 49 , 51 , 52 , 54 , 56 – 60 ] were of moderate quality, whereas three of them (25%) [ 50 , 53 , 55 ] were of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity between groups: p = 0.016 LR Test: RE vs FE chi^2 = 457.902, p = 0.000); Coleman et al [17] Wilkinson et al [60] Junkum et al [54] Sattabongkot et al [43] Poolphol et al [41] Green et al [19] Sriwichai et al [44] 2001−2010 Gingrich et al [38] Upatham et al [59] Rosenberg et al [15] Rattanarithikul et al [16] Limrat et al [40] Study 2011−2021 Sumarnrote et al [46] Carrara et al [50] Tainchum et al [47] LR Test: RE vs FE chi^2 = 129.366, p = 0.000)…”
Section: Anopheles Vectors For Plasmodium Speciesmentioning
confidence: 99%
“…A malaria sporozoite antigen panel assay for detection of malaria parasites in mosquitoes has been developed and marketed by VecTOR Test Systems, Inc. with Army SBIR funding, and overseas DoD laboratories have tested the assay for sensitivity and specificity. A similar assay (called VecTest™) was previously manufactured by Medical Analysis Systems, Inc. (Sattabongkot et al 2004), and development of a VecTest™ used to identify West Nile virus and St. Louis encephalitis viral antigens in mosquitoes was also supported by U.S. Army SBIR funding. Other fielded non‐commercial assays used by the U.S. military to detect infectious diseases in vectors since 2004 include Rift Valley fever virus conventional and real‐time (RT) polymerase chain reaction (PCR) assays (used during the 2006‐2007 outbreak); chikungunya and O'nyong‐nyong conventional and RT PCR assays; sand fly fever conventional PCR assays (for Toscana, Naples, and Sicilian strains); Ndumu, Babanki, Bunyamwera, and Dugbe virus conventional PCR assays; and eastern equine encephalitis virus reverse transcription PCR assays (O'Guinn et al 2004).…”
Section: Vector and Vector‐borne Infectious Disease Identification Toolsmentioning
confidence: 99%